Estimating the generation of waste electrical and electronic equipment in organizations: The case of a Brazilian federal agency - Faria, Rodrigo da Silva; Souza, Ricardo Gabbay de [UNESP]; de Freitas, Jéssica Galdino; Vieira, Igor Laguna (Elsevier, 2021)
The generation of waste electrical and electronic equipment (WEEE) has become a globally serious problem. Its adequate management has great importance for governments and organizations alike. Despite the available literature on models for estimating WEEE generation, such analysis and forecasting are scarce in the context of big organizations. The objective of this research is to estimate WEEE generation in organizations using the Market Supply model applied to a Brazilian federal agency. The agency's Asset Control System was the data source. These records allow organizations to effectively manage their WEEE, influencing the quality of generation estimate. A statistical analysis was carried to calculate the lifespan of the equipment in the system, observing a reduction in the lifespan of the most modern items. The model allows for estimating WEEE generation for the coming years in organizations, whilst providing lifespan profiles, meaning the probabilistic obsolescence rate of appliances. The results obtained, including the statistical analyses and the used methodology represent a valuable resource to organizations as a means to inform their decision-making process regarding the management of WEEE.
Keywords: E-waste; EEE Lifespan; Estimation of WEEE Generation; Waste electrical and electronic equipment